Investigating the effect of mixing time on the crystallite size and lattice strain of the AA7075/TiC composites Einfluss der Mischzeit auf die KristallitgröÃe und die Gitterverzerrung von AA7075/TiC-Verbundwerkstoffen - Alam, M.A. (John Wiley and Sons Inc, 2021)
With numerous reinforcements, aluminum and its alloys are finding growing applications in every sector of industry. Titanium carbide (TiC) is regarded as an outstanding reinforcing material as compared to widely used carbide particles because of its excellent physical and mechanical characteristics, as well as its especially good interfacial bonding (wetting) capacity with aluminum. In the present research work, the effect of the mixing time of the matrix and reinforcement powders has been investigated on the crystallite size and lattice strain of the AA7075â5 wt. TiC composites. The mechanical properties of the developed composites were also investigated in terms of microhardness values. X-ray diffraction and scanning electron microscopy (SEM), transmission electron microscopy (TEM), particles size distribution analysis and x-ray energy dispersive spectroscopy (EDS) of the synthesized powder samples were done to see the effect of mixing time on their microstructures. The increase in mixing time led to a homogeneous distribution of 5 wt. of TiC particles, a decrease in particles clustering. The considerable grain refining was confirmed, which reflected a reduction in particle size originating from a prolonged mixing time. The significant improvement in the crystallite size and microhardness of the produced composites were achieved with increasing mixing time. Â© 2021 Wiley-VCH GmbH